2013
DOI: 10.1177/0956797613499923
|View full text |Cite
|
Sign up to set email alerts
|

How Bad Could It Be? Alcohol Dampens Stress Responses to Threat of Uncertain Intensity

Abstract: Stress response dampening is an important motive for alcohol use. However, stress reduction via alcohol (alcohol SRD) is observed inconsistently in the laboratory, and this has raised questions about the precise mechanisms and boundary conditions for these effects. Emerging evidence indicates that alcohol SRD may be observed selectively during uncertain but not certain threats. In a final sample of 89 participants, we measured stress response via potentiation of defensive startle reflex in response to threat o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 33 publications
7
121
0
Order By: Relevance
“…The NPU task has been used to examine drug administration and deprivation effects on negative affective response 4,34 and etiological mechanisms in mood and anxiety disorders [22][23][24][41][42][43] . In other research, Curtin and colleagues have also developed variants of these cued threat tasks that precisely manipulate threat uncertainty about WHEN (shock timing) 5,29,44 ; WHERE (administration location on body for shock) 25 ; and HOW BAD (shock intensity) 7 . While Curtin et al's use of these tasks has thus far focused on the effects of drug administration and withdrawal in healthy participants; all of these tasks could be used to study anxiety and fear responses in patients with anxiety and other mental disorders Curtin and colleagues have used all of the aforementioned classes of cued threat tasks in a program of research that has probed the boundary conditions of alcohol's anxiolytic effects on anxiety expressed during uncertain threat, broadly defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NPU task has been used to examine drug administration and deprivation effects on negative affective response 4,34 and etiological mechanisms in mood and anxiety disorders [22][23][24][41][42][43] . In other research, Curtin and colleagues have also developed variants of these cued threat tasks that precisely manipulate threat uncertainty about WHEN (shock timing) 5,29,44 ; WHERE (administration location on body for shock) 25 ; and HOW BAD (shock intensity) 7 . While Curtin et al's use of these tasks has thus far focused on the effects of drug administration and withdrawal in healthy participants; all of these tasks could be used to study anxiety and fear responses in patients with anxiety and other mental disorders Curtin and colleagues have used all of the aforementioned classes of cued threat tasks in a program of research that has probed the boundary conditions of alcohol's anxiolytic effects on anxiety expressed during uncertain threat, broadly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers interested in anxiety and fear acquisition, rather than expression, can modify the instructions and stimulus parameters in the Threat Probability Task to better serve their research questions. As noted earlier, retrospective self-report of anxiety/fear after each set or at the end of the task can be obtained easily 7 . Online measurement of perceived shock likelihood can also be obtained via keyboard press or voice recording to ensure that participants maintain attention and understanding of instructions throughout the task (for an example see 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, evidence from threat-of-shock paradigms has suggested that uncertainty elicits defensive motivation, which is associated with increased physiological reactivity and hypervigilance. For example, the startle reflex-a somatic marker of defensive motivation (Lang, Bradley, & Cuthbert, 1992)-is enhanced during the anticipation of unpredictable as compared to predictable shocks (Bradford, Shapiro, & Curtin, 2013;Grillon, Baas, Lissek, Smith, & Milstein, 2004;Hefner & Curtin, 2012;Shankman, Robison-Andrew, Nelson, Altman, & Campbell, 2011), and fMRI research involving similar contrasts has indicated sustained hyperactivity in attentional networks (Carlsson et al, 2006;Hasler et al, 2007). Consistently, unpredictable threat of shock facilitates early perceptual and attentional processing, even with uncertainty-independent neutral stimuli (Baas, Milstein, Donlevy, & Grillon, 2006;Cornwell et al, 2007;Nelson, Hajcak, & Shankman, 2015;Shackman, Maxwell, McMenamin, Greischar, & Davidson, 2011).…”
mentioning
confidence: 99%